Response to commentary article: "The association between Interleukin-1β gene rs1143634 polymorphism and the risk of breast cancer by Bei Wang, Fenlai Yuan". (January 2019) - Pooja, Singh; Rajender, Singh; Konwar, Rituraj
Abstract: This a response to the commentary article entitled "The association between Interleukin-1β gene rs1143634 polymorphism and the risk of breast cancer" by Bei Wang, Fenlai Yuan. We completely agree with Wang and Yuan that there is significant deviation of HWE in control subjects for IL-1beta exon 5 +3954 polymorphism. Therefore, the apparent genetic association in IL-1beta exon 5 +3954 polymorphism must be used cautiously for further interpretation.